The “ins” and “outs” of product and services marketing: The influence of consonant wanderings in consumer decision-making - Godinho, S. (2020)
The established preference for words featuring consonants ordered inward in the oral cavity—the in–out effect, may assist marketeers when naming new products and services. To investigate the conditions under which this effect may affect consumer preference we conducted four experiments (N = 818) examining the influence of consonant wanderings in the evaluation of different professionals and food products. While inward articulation direction selectively biased warmth judgments about workers who are perceived as relatively neutral on both warmth and competence, for professionals traditionally associated with either a warmth or a competence dimension inward-wandering usernames systematically presented a competitive advantage. In the same way, hypothetical food products with inward-wandering names were judged as more hedonic and more utilitarian. The present evidence supports the potential of the in–out effect to market products and services and highlights the relevance of exploiting this and other oral kinematics phenomena as an asset for managerial practice.